Plant-mediated effects of drought on aphid population structure and parasitoid attack - Aslam, T. J.; Johnson, S. N.; Karley, A. J. (Journal of applied entomology (1986), 2013)
The effects of predicted climate change on aphid–natural enemy interactions have principally considered the effects of elevated carbon dioxide concentration and air temperature. However, increased incidence of summer droughts are also predicted in Northern Europe, which could affect aphid–plant interactions and aphid antagonists. We investigated how simulated summer drought affected the bird cherry–oat aphid, Rhopalosiphum padi L., and its natural enemy the parasitoid wasp Aphidius ervi. Drought and, to a greater extent, aphids reduced barley ( Hordeum vulgare) dry mass by 33% and 39%, respectively. Drought reduced leaf and root nitrogen concentrations by 13% and 28%, respectively, but foliar amino acid concentrations and composition remained similar. Aphid numbers were unaffected by drought, but population demography changed significantly; adults constituted 41% of the population on drought‐treated plants, but only 26% on those receiving ambient irrigation. Nymphs constituted 56% and 69% of the population on these plants, respectively, suggesting altered aphid development rates on drought‐stressed plants. Parasitism rates were significantly lower on drought‐stressed plants (9 attacks h−1 compared with 35 attacks h−1 on ambient‐irrigated plants), most likely because of lower incidence of nymphs and more adults, the latter being more difficult to parasitize. Any physiological changes in individual aphids did not affect parasitoid preferences, suggesting that attacks were postponed because of drought‐induced changes in aphid demography. This study demonstrates the potential for sporadic climate change events, such as summer drought, to be disruptive to herbivore–antagonist interactions.